Examination of Y-chromosomal microdeletions and partial microdeletions in idiopathic infertility in East Hungarian patients - Attila Mokánszki; Anikó Ujfalusi; Éva Gombos; István Balogh (Wolters Kluwer Medknow Publications, 2018)
Purpose: The aim of this study was to establish the Y chromosome microdeletion and partial AZFc microdeletion/duplication frequency firstly in East Hungarian population and to gain information about the molecular mechanism of the heterogeneous phenotype identified in males bearing partial AZFc deletions and duplications. Materials and Methods: Exactly determined sequences of azoospermia factor (AZF) region were amplified. Lack of amplification was detected for deletion. To determine the copy number of DAZ and CDY1 genes, we performed a quantitative analysis. The primers flank an insertion/deletion difference, which permitted the polymerase chain reaction products to be separated by polyacrylamide gel electrophoresis. Statistical Analysis Used: Mann-Whitney/Wilcoxon two-sample test, Kruskal-Wallis test, and two-sample t-probe were used for statistical analysis. Results: AZFbc deletion was detected only in the azoospermic cases; AZFc deletion occurred significantly more frequently among azoospermic patients, than among oligozoospermic males. The frequency of gr/gr deletions was significantly higher in the oligozoospermic patients than in the normospermic group. The b2/b3 deletion and partial duplications were not different among our groups, while b1/b3 deletion was found only in the azoospermic group. In infertile males and in normozoospermic controls, similar Y haplogroup distribution was detected with the highest frequency of haplogroup P. The gr/gr deletion with P haplogroup was more frequent in the oligozoospermic group than in the normozoospermic males. The b2/b3 deletion with E haplogroup was the most frequent, found only in the normozoospermic group. Conclusions: Y microdeletion screening has prognostic value and can affect the clinical therapy. In case of Y chromosome molecular genetic aberrations, genetic counseling makes sense also for other males in the family because these types of aberrations are transmittable (from father to son 100% transmission).